(untitled) (Vietnam Journal of Community Medicine, 2021)
Objectives: To evaluate the scientific evidence related to the failure rate of extra-alveolar bone mini-implant in orthodontic. Materials and methods: An electronic searched for articles on the databases PubMed, ScienceDirect, Google Scholar to identify all peer-reviewed articles potentially relevant to the review based on PIOCS framework. Methodological limitations were highlighted and the quality of articles was scored using tools such as: Risk of Bias in Non-randomized Studies - of Interventions (ROBINS-I) for cohort studies and Cochrane Risk of Bias Tool for randomized controlled clinical trials. Meta-analysis was conducted with selected article. RESULTS: Sample sizes of each study ranged from 30 to 840 patients, with 55 to 1680 mini-implants. Most of studies used 2 mm diameter and 8-12 mm length mini-implants, immediately loaded with 8-14 oz. The failure rate of IZC mini-implant ranged from 6.3% to 27.3% while this percentage of BC mini-implant was 7.2% to 68.7%. The meta-analysis showed that there was no significant relationship of the failure rate between the left and the right side. Conclusion: Althought the failure of extra-alveolar bone mini-implant was low in almost research, it needs more randomized controlled clinical trial studies to evaluate exactly.